Effect of gemfibrozil in vitro on fat-mobilizing lipolysis in human adipose tissue. - Carlson, L. A. (1976)
Fat-mobilizing lipolysis was studied in rat and human adipose tissue during incubation in vitro by following the release of glycerol into the incubation medium. Gemfibrozil as well as clofibrate consistently and readily inhibited basal as well as noradrenaline-stimulated fat-mobilizing lipolysis in rat fat. With human adipose tissue no effect was observed with gemfibrozil and clofibrate on basal lipolysis. This may be due to the comparatively low rate of the nonstimulated fat-mobilizing lipolysis in human tissue incubated in vitro. When lipolysis was stimulated with noradrenaline as well as isoprenaline, however, both gemfibrozil and clofibrate significantly reduced the fat-mobilizing lipolysis. This inhibition of lipolysis was however not observed in all studies. When lipolysis had been stimulated with theophylline, no inhibition of lipolysis was obtained with either compound. The possibility that reduced fat-mobilizing lipolysis in adipose tissue may cause a lowering of plasma triglycerides by reducing the flow of FFA to the liver is discussed in some detail. It is also suggested that inhibition of lipolysis may be accompanied by increased activity of lipoprotein lipase as well as an increase in the FIAT process. However, the pharmacological implication of the above-mentioned findings, particularly for gemfibrozil, must await further studies, as fairly large doses, around 1 mg/ml of incubation medium, were needed to obtain inhibition of fat-mobilizing lipolysis.